Pendampingan Digital Marketing Produk UMKM Desa Manggihan Kabupaten Semarang - Budi Hartono; Veronica Lusiana; Kristiawan Nugroho; Mohammad Riza Radyanto (Institut Teknologi dan Bisnis Semarang, 2024)
Located in Getasan subdistrict, Semarang district, Manggihan village has 506 families. Most of the population works as farmers, cattle breeders and entrepreneurs. The problem faced is that micro, small and medium enterprises (MSMEs) cannot market their products widely. The superior products are mushroom chips, onion crackers and processed catfish. Marketing of these products experienced a decline in turnover during the Covid 19 Pandemic. The solution to this problem is to provide MSME partners who are affected by the pandemic through digital marketing assistance. Empowerment through this assistance involves various elements: academics (Lecturers, Unisbank Semarang Students), government (Semarang Village and Regency Government), business (farmers, MSMEs, digital marketing providers). The method used to solve this problem uses business assistance through digital marketing training with social media, creating market place accounts, logo branding and etiquette. The output target that partner MSMEs want to achieve is helping increase turnover through post-pandemic digital marketing and strengthening product branding and expanding markets